Analysis Of Implementation Of Fixed Asset Accounting According To Psak No. 16 In Pt Gajah Tunggal Tbk - Diah Aryati Prihartini; Early Armein (International Journal of Science, Technology & Management, 2021)
In supporting the company's growth and development activities to achieve its goals, the company requires an asset or assets. Assets are a form of wealth and resources owned by the company. Fixed assets have a very important position in the company so that it can run well. The purpose of this study was to determine the suitability of the application of fixed asset accounting at PT Gajah Tunggal Tbk to the recognition of property and equipment, measurement of the time of disclosure of property, plant and equipment, measurement after disclosure of property, plant and equipment, derecognition of property and equipment, and disclosure of property, plant and equipment compared to PSAK No. 16. The data used in this scientific writing is Secondary Data in the form of information regarding the Accounting Application of Fixed Assets of PT Gajah Tunggal Tbk in the 2019 Financial Statements. The data analysis method used in this scientific writing is the descriptive-comparative analysis method. From the results of this study, it can be concluded that PT Gajah Tunggal Tbk in carrying out its Fixed Assets accounting policies in accordance with PSAK No. 16 but PT Gajah Tunggal Tbk has not adopted PSAK No. 16 in its financial statements. The author assumes the application of accounting by PT Gajah Tunggal Tbk regarding PSAK No. 16 has complied with financial accounting standards. Therefore, the application of accounting for PT Gajah Tunggal's fixed assets must be maintained, carried out effectively and the company can adopt PSAK 16 in its financial statements.